Nanostructured FeNi-based magnetic materials - Xiao, Junjing (2010)
Soft magnetic materials like Ni-Fe based alloys exhibit low coercivity, high saturation magnetization and high permeability. More interestingly is their improved performance when reduced to nano-scale due to the lack of influence from magnetic walls. They are particularly useful for applications like transformer cores, inductors and magnetic shielding. This project investigates the relationship between the structural and magnetic properties of nanocrystalline Mumetal (Ni0.77 Fe0.16 Cu0.05 Cr0.02) and milling time. Nanocrystalline Mumetal powders were synthesized by mechanical alloying process using a planetary ball-mill under argon atmosphere for a range of periods between 1~96 hrs. Alloy formation was studied using X-ray diffraction (XRD) technique and Scanning Electron Microscopy (SEM). The magnetic properties were investigated using Vibrating Sample Magnetometer (VSM). Complete formation of the alloy phase, γ- (Fe, Ni, Cu, Cr), was observed after a milling period of 12 hrs. The change in the powder morphology was studied using the SEM and a gradual transition to spherical powder shape was seen. Increasing lattice parameter and decreasing grain size were also observed with increasing milling time. Similarly, saturation magnetization, coercivity and retentivity values obtained from the VSM (hysteresis curve) reflected increasing magnetization, decreasing coercivity and retentivity with milling.